Efficacy of two delivery modes of behavioral self-management in severe chronic fatigue syndrome. Issue 3 (2nd July 2016) - Friedberg, Fred; Adamowicz, Jenna; Caikauskaite, Indre; Seva, Viktoria; Napoli, Anthony
ABSTRACT: Purpose: To assess the efficacy of fatigue self-management for severe chronic fatigue syndrome (CFS). Methods: This randomized trial enrolled 137 patients with severe CFS. Participants were randomized to one of three conditions: fatigue self-management with web diaries and actigraphs (FSM:ACT); fatigue self-management with less expensive paper diaries and pedometers (FSM:CTR); or an usual care control condition (UC). The primary outcome assessed fatigue severity at 3-month follow-up. Analysis was by intention-to-treat. Results: At 3-month follow-up, the FSM:CTR condition showed significantly greater reduction in fatigue severity compared to UC ( p = .03; d = .58). No significant improvement was found at 12-month follow-up for the FSM:ACT or the FSM:CTR condition as compared to UC ( p > .10). The combined active treatment conditions revealed significantly reduced fatigue at 3-month follow-up ( p = .03), but not at 12-month follow-up ( p = .24) compared to UC. Clinically significant improvements were found for 24–28% of the intervention groups as compared to 9% of the UC group. Attrition at 12-month follow-up was low (< 8%). Conclusion: Home-based self-management for severe CFS appeared to be less effective in comparison to findings reported for higher functioning groups. Home-based management may be enhanced by remotely delivered interventional feedback.